Penjadwalan Berbasis Risiko dengan Program Evaluation and Review Technique untuk Mendukung Implementasi BIM 4D pada Proyek Jembatan - Febrianti, Imelda; R. Winanda, Lila Ayu; Roostianawaty, Nenny; Kartika, Deviany; F. Anugerahputra, Krisna (Tadulako University, 2026)
The construction industry plays strategic role in national infrastructure development, particularly in bridge projects that are characterized by high complexity and significant implementation uncertainty. Bridges function not only as physical connections between regions but also as critical infrastructure supporting public mobility and economic growth. Therefore, accurate scheduling methods that are capable of accommodating the risk of time delays are required. This study to analyze the total project duration of bridge project risk-based approach through the integration of three-dimensional Building Information Modeling (BIM 3D) and the Program Evaluation and Review Technique (PERT). The analysis begins with the development of three-dimensional bridge structural model using Tekla Structures to generate bill of quantity that includes structural material volumes. These quantity data basis for probabilistic duration estimation using PERT method through expert judgment, which involves optimistic time, most likely time, and pessimistic time. The BIM 3D modeling results indicate total reinforcement steel volume of 24,343.4 kg and concrete volume of 274.1 m³. Furthermore, risk-based scheduling using the PERT method analyzed with the Precedence Diagram Method (PDM) produces total project duration of 190 days with completion probability of 50%. This result indicates potential risk of delay that should carefully project time control